I'm mistified about where I'm going wrong here:
Find the derivative of: [(4x-1)(4x-1)^1/2]
The answer given is 6(4x-1)^1/2
but I get 6(4x -1)
not sure where i'm going wrong if anyone could help that would be great!
Thanks, that makes perfect sense.
could you explain what's wrong with my method please?
u = 4x-1
u' = 4
v = (4x-1)^1/2
v' = 2/[(4x-1)^1/2]
using product rule --
4(4X-1)1/2 + 2(4x-1)/[(4x-1)^1/2]
multiplying through by (4x-1)^1/2
4(4x-1) + 2(4x-1) = 24x-6 = 6(4x-1)
I know i'm going wrong somewhere..I just can't see where!